Innovation Learning Process in New Normal Era: Effectiveness of Online Proctored Examination (OPE) Technology to Increase Student Honesty in Physics Lecture - Herliana, Fitria; Saputri, Mawarni; Mahzum, Elmi; ., Musdar (KnE Social Sciences, 2024)
This study aims to determine the effectiveness of online proctored examination (OPE) technology in increasing students’ honesty levels. This research is a pre-experiment using one group pre-test and post-test design methods. OPE in Physics lectures was conducted on a group of randomly chosen 34 students. The level of honesty of students was measured using the autoproctor application, which is used in the implementation of the OPE. Then, the level of honesty before using OPE at meeting 1 was compared with after getting used to using OPE at meeting 6. The data were analyzed using paired sample t-tests and quantitative description. The results show that OPE technology was effective in increasing students’ honesty levels. This is indicated by the results of the paired sample t-test using the Wilcoxon test of 72.5 with a p-value of < 0.001. In addition, the average increase in the pre-test and post-test honesty scores recorded by the autoproctor application was 64.9% for the pre-test and 92.6% for the post-test. The effectiveness of OPE in learning is supported by the results of responses to a questionnaire that measures the relative advantage, compatibility, ease of use, trialability, and observability of using OPE. The results of the questionnaire responses show an average score of 78.7, namely the use of OPE was classified as effective in learning. The results of this study can be used as a reference for teachers and academic practitioners to increase the level of honesty of students in online exams using OPE technology. Keywords: innovation learning process, OPE Technology, Student Honesty